2019
DOI: 10.1371/journal.pone.0227066
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of circulating cell-free DNA (cfDNA) in urine using a newborn piglet model of asphyxia

Abstract: Cell free DNA (cfDNA) in plasma has been described as a potential diagnostic indicator for a variety of clinical conditions, including neonatal hypoxia. Neonatal hypoxia or perinatal asphyxia is a severe medical condition caused by a temporary interruption in oxygen availability during birth. Previously, we have reported temporal changes of cfDNA detected in blood in a newborn piglet model of perinatal asphyxia. However, cfDNA can also be found in other body liquids, opening for a less invasive diagnostic pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The assumption of a disease-dependent spread of DNA fragments is counteracted by the observation of base-line levels of cfDNA detected in the blood circulation of healthy individuals, with age, sex, hormonal, biorhythmic, and other dependencies [11]. Further, cfDNA fragments are not only circulating in blood, but can also be found in other body fluids, like saliva, urine, or cerebrospinal fluid [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The assumption of a disease-dependent spread of DNA fragments is counteracted by the observation of base-line levels of cfDNA detected in the blood circulation of healthy individuals, with age, sex, hormonal, biorhythmic, and other dependencies [11]. Further, cfDNA fragments are not only circulating in blood, but can also be found in other body fluids, like saliva, urine, or cerebrospinal fluid [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many different markers have been proposed to estimate the oxidative stress reactions and cell damages in its pathophysiological background; however, the key regulatory elements are still not identified [12]. Studies have proposed that cfDNA might be an early indicator of perinatal asphyxia [12,13]. Moreover, Tuaeva et al, 2008 observed that premature birth is associated with increased cfDNA concentrations in the blood of neonates [26].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations